Stenochlaena palustris aqueous extract reduces hepatic peroxidative stress in Marmota caligata with induced fever - Adenan, Adenan; Suhartono, Eko (Universa Medicina, 2010)
The kelakai fern (Stenochlaena palustris) contains bioactive substances, such as flavonoids, steroids, and alkaloids. The kelakai is used by the Kenyah Dayak communities for the treatment of anemia, fever, and cutaneous disorders. Fever is increased temperature regulation of the body, which process indirectly increases the production of peroxides, leading to peroxidative stress. The aim of this research study was to evaluate the influence of an aqueous extract of the kelakai fern on peroxidative stress in the hoary marmot (Marmota caligata) with experimentally-induced fever. This was a true experimental study, with post test-only and control group design, involving 6 groups, each made up of 4 animals. Peroxide concentration was measured by a modification of the FOX2 method and peroxidase activity by the Kanehira method. The kelakai extract was administered to the animals by gavage at weight-adjusted dosages between 7.75 x 10-4 mg/kg body weight to 1.24 x 10-2 mg/kg body weight. Data were analyzed using singe linear regression test. The results showed that kelakai extract dose significantly reduced the peroxide levels, regression equation with the Y = 2.513-106.03 X (R2 = 0.8057), indicating that 80.5% variation of peroxide levels is predicted by the kelakai extract dose. From the results we conclude that kelakai aqueous extract decreases peroxide levels in hoary marmots with experimentally-induced fever.